KINETIKA INTERAKSI ION Cr6+ DENGAN FITOPLANKTON LAUT (Tetraselmis chuii) - Jayali, Ahmad Muchsin (Green Earth, 2012)
The research aimed to examine the ability of bioaccumulation of Cr6+ by marine phytoplankton Tetraselmis chuii as water bioindicators. The analysis method used was Atom Absorption Spectrophotometer (AAS). The results of research indicate that the optimum growth time of Tetraselmis chuii phytoplankton for 10 days with maximum cell density as big as 1.850.000 cells/mL phytoplankton. Maximum concentration ion Cr6+ that can be tolerated (MTC) by Tetraselmis chuii phytoplankton is 0.250 ppm. Bioaccumulation ion Cr6+ in marine phytoplankton Tetraselmis chuii follow orde-1 mechanism with optimum time of 30 minutes at Tetraselmis chuii. intake constant velocity of k1 in a row is 0.0120/minutes. Constant release rate velocity of k2 in a raw is 0.0003/minutes. Key words : Kinetics, ion, chromium, T.chuii.